Mathematical Modelling and Computer Simulation Assist in Designing Non-traditional Types of Precipitators and Separators - Milan Bernat; Jaroslav Džmura; Renáta Bernátová; Ľubomr Žáčok; Jan Pavlovkin (Institute of Advanced Engineering and Science, 2018)
The article deals with the application of the method for mathematical modeling and simulation at solving some issues in the area of electrostatic technology. It focuses on the processes in electrostatic separation and precipitation. Computer simulation is highly required for equipment design and for their diagnostics in critical operating states using theoretical calculations and experimental data evaluation. The presented computer models may be applied both by project and design engineers using the most advanced computer-aided design of electrostatic technologies.